Da impotência à impossibilidade: a escrita do objeto a na pornografia de Hilda Hilst - Morel, Kátila Kristhina Kormann (2013)
In 1990, Hilda Hilst announces she would be leaving serious literature and would write pornografphy to earn money and readers. However, since the 1970s, there is in her speech a declared tension between what she writes and what editors and readers would like her to write. From the viewpoint of lacanian psychoanalysis, it can be said that in this speech is in question the attempt always impossible of satisfying the demand of the Other. Such discourse permeates the work of Hilda Hilst, so much so that her first prose tale, "Fluxo", has writing as a theme and as in line with his speech, the character Ruiska, writer, is also trying to satisfy the demand of the Other. Faced with this impasse between what he would like to write and what the editor required, Ruiska succumbs and goes mad. When Hilda Hilst announces she would write porn, she seems to have yielded to the pleas of publishers and would offer the target-object, object demanded. Various aspects of pornography make it operate via the sense, leading to an enjoyment of sense and thus getting the level of demand. However, Hilda Hilst, in the book O caderno rosa de Lori Lamby , subverts the usual procedures of pornography that would take this to operate via the sense, making her pornographic writing operate by way of the enjoyment out-of-sense, making an edge to the actual passing of impotence and inability for allowing something that meshes of desire. Thus, Hilda Hilst´s pornography now functions as an anal object a, double-face, which seems to have the brightness agalma, but which is actually garbage.